1999
DOI: 10.2169/internalmedicine.38.486
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcemia Accompanied by Hypothalamic Hypopituitarism, Central Diabetes Inspidus and Hyperthyroidism.

Abstract: Wepresent here a case of prominent hypercalcemia accompanied by hypothalamic tumor and Graves' disease. A24-year-old manwith hypothalamic tumor showed hypopituitarism, central diabetes inspidus (DI) and hyperthyroidism. Nausea, loss of thirst and appetite, and general fatigue were found with the unveiling of hypercalcemia and hypernatremia. Parathyroid hormone (PTH) and la-dihydroxyvitamin D levels were suppressed with a normal range of PTHrelated protein values. One-desamino-(8-D-arginine)-vasopressin (DDAVP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Excess thyroid hormone stimulates bone resorption, which is partially inhibited by cortisol (23,24). There have been some case reports of patients who concomitantly exhibited adrenal insufficiency and thyroid disorders, such as thyrotoxicosis (12,(25)(26)(27) and hypothyroidism (28,29). However, in this study, there was no patient under immobilization or who had thyroid dysfunction before the onset of hypercalcemia.…”
Section: Discussionmentioning
confidence: 60%
“…Excess thyroid hormone stimulates bone resorption, which is partially inhibited by cortisol (23,24). There have been some case reports of patients who concomitantly exhibited adrenal insufficiency and thyroid disorders, such as thyrotoxicosis (12,(25)(26)(27) and hypothyroidism (28,29). However, in this study, there was no patient under immobilization or who had thyroid dysfunction before the onset of hypercalcemia.…”
Section: Discussionmentioning
confidence: 60%
“…In another case report, a 24-year-old male patient presenting with hypercalcemia and hypernatremia was diagnosed with hypopituitarism, diabetes insipidus and GD. [16] More recently, the potential coexistence of TSH-secreting pituitary adenomas and autoimmune hypothyroidism, [17] GD and macroprolactinoma [18] and GD and lymphocytic hypophysitis has been reported. [19,20] In cases of acromegaly, the presence of goiter is 59.2%; however, overt hyperthyroidism develops in 8.6% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Maruyama et al (16) reported that transient thyrotoxicosis developed after cessation of steroid therapy in a patient with autoimmune thyroiditis and rheumatoid arthritis, and plasma cortisol concentration was 6.7 μg/dL when thyrotoxicosis developed. Wada et al (17) reported the simultaneous occurrence of hyperthyroidism and ACTH deficiency due to a hypothalamic tumor. Takasu et al (18) reported that there were exacerbations of autoimmune thyroid dysfunction during the period of glucocorticoid tapering after unilateral adrenalectomy in patients with adrenal Cushing's syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Neurologic examinations revealed no abnormalities. Laboratory findings were as follows: white blood cells 5,900/mm 3 (reference range: 4,300-10,800), blood urea nitrogen 18.4 mg/dL (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), creatinine 0.7 mg/dL (0.5-1.3), sodium 135 mEq/L (136-146), potas- -20). The urine volume was 1,800 mL/day.…”
Section: Case Reportmentioning
confidence: 99%